Simulation-enhanced lean design process - Jon H. Marvel; Charles R. Standridge (Journal of Industrial Engineering and Management (JIEM), 2009)
A traditional lean transformation process does not validate the future state before implementation, relying instead on a series of iterations to modify the system until performance is satisfactory. An enhanced lean process that includes future state validation before implementation is presented. Simulation modeling and experimentation is proposed as the primary validation tool. Simulation modeling and experimentation extends value stream mapping to include time, the behavior of individual entities, structural variability, random variability, and component interaction effects. Experiments to analyze the model and draw conclusions about whether the lean transformation effectively addresses the current state gap can be conducted. Industrial applications of the enhanced lean process show it effectiveness.
Keywords: 650; lean manufacturing; simulation; process design